Hubungan antara Mental Toughness dan Competitive Anxiety pada Atlet Taekwondo Pegasus Indonesia di Kota Jambi - Anjar Kinanti; Grafitte Decheline; Bangkit Yudho Prabowo (SPRINTER: Jurnal Ilmu Olahraga, 2026)
The study aims to analyze the relationship between mental toughness and competitive anxiety in Indonesian Pegasus Taekwondo athletes in Jambi City. This study used a quantitative method with a correlational design. The study sample consisted of 22 athletes selected using a total sampling technique. The mental toughness instrument refers to the concept developed by Daniel F. Gucciardi, while competitive anxiety was measured using the Sport Anxiety Scale (SAS). Data analysis included descriptive statistics, the Kolmogorov-Smirnov normality test, and the Pearson Product Moment correlation test. The results showed that the athletes' mental toughness level was in the moderate category with a mean value of 102.05 and a standard deviation of 4.27. Meanwhile, the level of competitive anxiety was also in the moderate category with a mean of 47.6 and a standard deviation of 5.195. The results of the normality test showed that the data were normally distributed (Asymp. Sig = 0.200 > 0.05). The correlation analysis showed a significant negative relationship between mental toughness and competitive anxiety. This means that the higher the athlete's mental toughness, the lower the level of competition anxiety they experienced. This finding confirms the importance of developing psychological aspects in improving the performance of taekwondo athletes.